Introversion and extroversion influence in students' verbal communicative competence - Alvarenga Martínez, Marta Isabel; Garay Castillo, Laura Karina; Martínez Orantes, Thammy Yesenia; Méndez Méndez, Ulises Antonio; Oliva, José Israel; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2011)
In El Salvador learning a second language has become an essential need in the last few years. According to Randstad (2011), worldwide Human Resources service provider, in El Salvador the 20% of the job opportunities managed by this company during 2010 included English as a requirement to get the position. Facts such as these make young people to choose those careers that include English in their curricula. This demand has been noticeable in the careers offered by the Foreign Language Department at the University of El Salvador. One of these is Licenciatura en Idioma Ingles Opción Enseñanza, which in the last four years has increased the number of its admitted students, becoming a problem for the Foreign Language Department because it does not count with the appropriate infrastructure to satisfy this demand. As a result, this has caused the overpopulation in the number of enlisted students for each English class groups, turning the teaching of English language hard.
Thesis in order to obtain the degree of -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2011
La tesis también está en formato digital.
Keywords: Lenguaje y lenguas -- Enseñanza